2021
DOI: 10.22323/2.20070206
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the impact of the COVID-19 pandemic on the work of science journalists: global perspectives

Abstract: The article presents the results of a survey of science journalists from six world regions about their work during the COVID-19 pandemic. The responses show perception of increasing workload for most participants. Local scientists and peer-reviewed articles are the main sources. According to the respondents, scientists have become more available during the pandemic. The use of preprint articles was a frequent practice, but a considerable proportion declared they did not adopt different procedures when reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
6
20
0
2
Order By: Relevance
“…Journalists also reported concern that their audiences might misunderstand what preprints are, a concern they attempted to address by offering definitions and context in their articles. Again, this aligns with findings from surveys by Massarani and colleagues 40,41 . However, this effort stands in contrast to those of recent content analyses, which found that journalists inconsistently identify scholarship mentioned in news articles as preprints, often describing it as "research" or simply hyperlinking to it 13,38 , and only sometimes explain what the term "preprint" means 14 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Journalists also reported concern that their audiences might misunderstand what preprints are, a concern they attempted to address by offering definitions and context in their articles. Again, this aligns with findings from surveys by Massarani and colleagues 40,41 . However, this effort stands in contrast to those of recent content analyses, which found that journalists inconsistently identify scholarship mentioned in news articles as preprints, often describing it as "research" or simply hyperlinking to it 13,38 , and only sometimes explain what the term "preprint" means 14 .…”
Section: Discussionsupporting
confidence: 89%
“…At best, they said, preprints offered potentially life-saving information at a time of great need; at worst, they contributed to misinformation among the public. These findings mirror the results of a survey of 633 science journalists from six world regions about their work during COVID-19, which found that 67% of US and Canadian journalists and 69% of European and Russian journalists had adopted different procedures to cover preprints during the pandemic 40 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Primero se exploran algunas discusiones sobre los roles normativos, es decir, el llamado 'deber ser' del periodismo en una pandemia. Luego se analizan las lógicas de la cobertura a partir de los temas, aspectos, actores y fuentes de información que usan los periodistas al informar una crisis sanitaria (Massarani et al, 2021;Mellado et al, 2021). Asimismo, se explora brevemente otro cuerpo de literatura que arroja luces sobre las situaciones riesgosas que enfrentan los periodistas en la cobertura de crisis, así como los primeros estudios que dan cuenta de las afectaciones sufridas por el impacto de COVID-19 en la salud y trabajo de los comunicadores alrededor del mundo.…”
Section: Estado Del Arte: Expectativas Normativas Vs Limitaciones Y Oportunidades En La Cobertura De Crisis Sanitariasunclassified
“…Esta prevalencia de las élites como fuentes primarias ha sido, de por sí, una tendencia en el periodismo de salud en diversos contextos (De Dobbelaer, Van Leuven & Raeymaeckers, 2018). Sólo el periodismo más especializado (Massarani et al, 2021), como los periodistas en ciencia que han cubierto la pandemia, han recurrido a científicos locales y a artículos evaluados por pares para documentar sus notas. En teoría, como sector informativo especializado, el periodismo de salud y de ciencia valora a las fuentes biomédicas como poseedoras de autoridad y conocimiento experto, ante su papel en la generación de conocimiento científico (Forsyth et al, 2012;Hallin et al, 2020).…”
Section: Seguimiento De Temas Actores Y Fuentes En Pandemiaunclassified